The status of the leech fauna (Annelida, Hirudinea) at the eastern region of Azerbaijan - Farzali, Shabnam; Saglam, Naim (Arak Univ, Arak, 2020)
This study was carried out between May 2017 and December 2019 to determine leech species in some wetlands in the Eastern region of Azerbaijan. In the research, the leech samples were collected from 21 locations from six wetlands in the eastern part of Azerbaijan. As a result of field and laboratory studies, five species of leeches were determined (Dina stschegolewi, Erpobdella sp., Haemopis sanguisuga, Hirudo orientalis, and Placobdella costata). In this research, Erpobdellid leech Erpobdella sp. are the first records from different three wetlands of Azerbaijan. In the freshwaters of Azerbaijan has been recorded 14 species of leeches. However, there are not detailed researches that these leech species are found in Azerbaijan. The freshwater leech fauna for the eastern region of Azerbaijan is determined for the first time in this research. P. costata and H. sanguisuga in two different, Erpobdella sp. in three various wetlands were found. However, D. stschegolewi and H. orientalis were determined only in one wetland. While Erpobdella sp coexists with P. costata in two water sources, it was observed that lives with H. orientalis in one wetland. H. sanguisuga and D. stschegolewi could not be detected with different leech species in water sources.
Keywords: Biodiversity; Erpobdellids; Haemopis; Hirudo; Placobdella